2015
DOI: 10.2116/analsci.31.1297
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Penetration and in vivo Distribution of Honokiol into the Intervertebral Disc in Rat

Abstract: Honokiol is a potential candidate for the treatment of intervertebral disc (IVD) degeneration. In this study, we develop in vitro and in vivo methods to detect the distribution of honokiol in intervertebral discs using high-performance liquid chromatography. A rat tail disc was used for both experimental models. For the in vivo animal experiment, blood samples and tail discs were collected at 15, 30, 60, 120 and 240 min after honokiol administration (30 mg/kg, i.v.). The analyte was separated by a mobile phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…A specific and sensitive ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method has been developed for the identification and quantification of myricetin in the rat plasma after oral and intravenous administrations, which indicated that myricetin would be poorly absorbed in the gastrointestinal tract, possibly due to its low water solubility, low stability in the gastrointestinal fluid and rapid biotransformation [ 300 ]. A validated reversed-phase HPLC method was developed to determine the in vitro penetration and in vivo distribution of honokiol into the IVD, suggesting that the penetration of honokiol into the IVD is sufficient to achieve a therapeutic concentration after honokiol administration [ 301 ].…”
Section: Perspectives Challenges and Practical Concernsmentioning
confidence: 99%
“…A specific and sensitive ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method has been developed for the identification and quantification of myricetin in the rat plasma after oral and intravenous administrations, which indicated that myricetin would be poorly absorbed in the gastrointestinal tract, possibly due to its low water solubility, low stability in the gastrointestinal fluid and rapid biotransformation [ 300 ]. A validated reversed-phase HPLC method was developed to determine the in vitro penetration and in vivo distribution of honokiol into the IVD, suggesting that the penetration of honokiol into the IVD is sufficient to achieve a therapeutic concentration after honokiol administration [ 301 ].…”
Section: Perspectives Challenges and Practical Concernsmentioning
confidence: 99%
“…Animal experiments have shown that HKL has a therapeutic effect on IDD. Chen et al [ 77 ] used high-performance liquid chromatography to explore the distribution of HKL in rat intervertebral discs. In vitro analysis showed that HKL diffusion into the discs was concentration-dependent.…”
Section: Natural Pharmacological Productsmentioning
confidence: 99%